2023
DOI: 10.1039/d3ra00094j
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 compact layer induced charge transfer enhancement in a three-dimensional TiO2–Ag array SERS substrate for quantitative and multiplex analysis

Abstract: A 3D TiO2–Ag array SERS substrate for rapid quantitative and multiplex analysis of pesticide residues for real samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…198–230 3D bottom-up self-assembly nanostructures are described owing to facile preparation and cost-effectiveness. 231–251 Combinatory detection is used for synergetic enhancements. 252–266…”
Section: Development Of Microdevices For Point-of-care Sers-based Bio...mentioning
confidence: 99%
“…198–230 3D bottom-up self-assembly nanostructures are described owing to facile preparation and cost-effectiveness. 231–251 Combinatory detection is used for synergetic enhancements. 252–266…”
Section: Development Of Microdevices For Point-of-care Sers-based Bio...mentioning
confidence: 99%
“…Solid substrates offer well-defined nanostructures that ensure the uniform and stable distribution of MNPs. As presented in Table 2 , various nanostructured solid substrates have been explored, including the Si micropyramid [ 119 ], Si nanowires [ 120 , 121 ], TiO 2 nanorods [ 122 ], polystyrene (PS) beads [ 123 ], microneedle [ 124 ], ZnO nanopillar [ 125 ], CuO nanorods [ 126 ], and UV curable resin [ 127 ]. In Figure 8 a, it can be observed that MNPs generate hotspots in the nanogaps between them.…”
Section: Design Fabrication and Applications Of Sersmentioning
confidence: 99%
“…Compared with single metal or semiconductor substrates, metal/semiconductor hybrids have many merits to produce high-efficiency SERS signals. The synergistic effect of electromagnetic enhancement and charge transfer can jointly improve the SERS activity. This phenomenon has been found in many metal/semiconductor hybrids, such as Au/CdS, Ag/GaN, and Au/TiO 2 hybrids. Meanwhile, the charge transfer efficiency between Raman probe and substrate can be further tuned due to the electron transfer and hot electron injection between metal and semiconductor, which can further improve the SERS activity. Since the SERS efficiency of metal/semiconductor hybrids is highly dependent on the component, architecture, some effective strategies have been proposed to optimize the SERS performance, such as tuning the metal morphology and adjusting the contact modes. However, in many metal/semiconductor nanohybrids, the huge near-field enhancement is usually hindered by a semiconductor shell. , Although the charge-transfer efficiency can be improved by plasmonic near-field enhancement, the electromagnetic field is greatly weakened, thus leading to limited SERS improvement. It still remains a challenge to design metal/semiconductor hybrids with simultaneous optimization of near-field enhancement and charge transfer for a highly improved SERS.…”
Section: Introductionmentioning
confidence: 99%